The linked photographers' guide to online marketing and social media - Adler, Lindsay; Sillars, Rosh.; Safari eBooks (Boston, Mass. : Course Technology, 2011)
"'The Linked Photographer's Guide to Online Marketing and Social Networking' is a complete resource for photographers looking to improve their business through social media. This book provides a step-by-step process for getting a photographer's business online, and acts as a reference guide for the variety of online marketing options on the web. This one-of-a-kind guide is the key to making social media work for the photographer to improve their business!"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Photographers -- Marketing; Photography -- Business methods; Internet marketing; Electronic books